Democratic Operation and Organization of the School Leadership - Giorgos, Dr Panagiotopoulos (International Journal of Scientific Research and Management (IJSRM), 2023)
This research study comes to highlight findings in relation to issues of democratic organization and operation of the school leadership. For the needs of the study, the quantitative methodology was followed and an electronic questionnaire (google form) was delivered through the Directorates of Primary Education of Greece to teachers’ emails. The sample, which was consisted of 358 individuals, was selected by following the simple random sampling technique. An electronic questionnaire with 14 close-ended questions was constructed, whereas there was also a session of demographic and vocational data including questions regarding gender, age, additional studies, years of service, and training in democratic operation and organization of school units. According to the findings, the participants do not state in a clear and unequivocal way whether they are satisfied or not with their participation in school decision-making, with the ability of students to influence school events or whether the Greek school can function in a democratic way. They somewhat agree that the school principal distributes responsibilities to the members of the school community, and treats equally all the staff members, as partners. Finally, statistically, gender, years of service, and training in issues of school democratic organization and functioning seem to affect some subscales.